(untitled) (Journal of Universal Science Research, 2024)
In this article, the implementation of new historical fundamental reforms in the fields of culture and art, as in all spheres of life of the people of Uzbekistan, was widely established. Problems accumulated in the field, namely, the management of the culture and art sphere, the formation of a qualified personnel training system and the development of its mechanisms, the strengthening of the material and technical base of educational institutions and professional theaters and other institutions of the industry in the field of culture and art, the social protection of artists and Art Workers of theater-concert organizations it has been mentioned that issues such as further improvement of the system are the most important tasks in the development of our national culture and art.